Effect of Iron Deficiency Anemia on HbA1c in Non-Diabetics - Bansal, R.K.; Yadav, Y.R.; Kulkarni, H.S.; Sonam, -; Garg, S.; Jain, P.; Sharma, V.K.; Maheshwari, S. (Journal of Diabetes and Endocrinology Association of Nepal, 2020)
Background: Glycated hemoglobin A1c is a well-known indicator of glycemic control in diabetes patients. It comprises of 5% of total hemoglobin in non-diabetic patients as well. Iron Deficiency Anemia is most common cause of anemia, especially in this part of the world. So, we study the effects of Iron deficiency Anemia on HbA1c levels in non-diabetic adults to determine whether the HbA1c levels increase if any. Methods: A 100 non-diabetic adult patients with Iron Deficiency anemia admitted in various medicine wards and attending OPDs of J.L.N. Medical College and 100 healthy controls were enrolled after fulfilled inclusion and exclusion criteria. Detailed history of clinical examination and biochemical examination was performed including HbA1c. Results: Mean HbA1c level is more in iron deficient Anemic non-diabetic patients in comparison to non-Anemic non-diabetic patients. Mean HbA1c is 5.01 ± 0.41 in control group. While mean HbA1c level in case group is 6.11 ± 0.42. The difference is statistically significant (p value <.001). Conclusion: Iron deficiency Anemia is independent factor affecting HbA1c level in non diabetic patients & it should be interpreted carefully in all iron deficient anemic patients.